1995
DOI: 10.1016/0005-2736(95)80021-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of rates of H+, Na+ and K+ transport across phospholipid vesicular membrane by the combined action of carbonyl cyanide m-chlorophenylhydrazone and valinomycin: temperature-jump studies

Abstract: Enhancement of delta pH relaxation rate by the combined action of valinomycin (VAL) and carbonyl cyanide m-chlorophenylhydrazone (CCCP) has been studied under a variety of concentration conditions in soyabean phospholipid (SBPL) vesicles after creating a pH gradient across the vesicular membrane delta pH by temperature jump. After taking note of the changes by VAL and CCCP induced membrane disorder (using nigericin and monensin mediated delta pH decay as probes) the following could be inferred about the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…At these concentrations neither valinomycin nor FCCP inhibits the P‐gp‐mediated efflux of drug [22]. It has previously been observed that FCCP and valinomycin in combination can precipitate in the presence of potassium [23,24]. However, under our experimental conditions, the FCCP concentration was 100‐fold higher than that of valinomycin.…”
Section: Drugs and Chemicalsmentioning
confidence: 68%
“…At these concentrations neither valinomycin nor FCCP inhibits the P‐gp‐mediated efflux of drug [22]. It has previously been observed that FCCP and valinomycin in combination can precipitate in the presence of potassium [23,24]. However, under our experimental conditions, the FCCP concentration was 100‐fold higher than that of valinomycin.…”
Section: Drugs and Chemicalsmentioning
confidence: 68%
“…[8][9][10] The magnitude of t depends on the size of the vesicles. 12 By monitoring the optical densities of vesicle suspensions at 700 nm the vesicle sizes were regulated such that the variation of t was within 20%. Reproducibility of relaxation traces (amplitudes and t) even after subjecting the same sample to several Tjumps confirmed that the integrity of vesicles was not affected and vesicles did not fuse due to T-jump in our experiments.…”
Section: Dph Decay Experimentsmentioning
confidence: 99%
“…If the rate limiting step of DpH decay is the translocation of a rate limiting species across the membrane with rate constant k r1 and if b i is the internal buffer capacity of vesicles. 8,10,12 1=t ÂŒ Ă°ln 10=b i Þk r1 Âœrate limiting species m Ă°1Þ…”
Section: Dph Decay Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the translocation of the M Ï© carriers Cal 2 MM or Cal 2 MH is the rate-limiting step it must be possible to increase the translocation rates (and 1/) by disturbing the membrane order such as by adding valinomycin at sufficiently high concentrations (Prabhananda and Kombrabail, 1995). The ⌬pH relaxation traces shown in Fig.…”
Section: Identification Of the Rate-limiting Stepmentioning
confidence: 99%